Implementasi Pendampingan Akuntansi Lingkungan dan Pencatatan Biaya Limbah di UD. Nur Jaya Kota Palopo - Tadjuddin; Muhammad Ikram; Jumarni; Susi Nilam Sari; Laila Ayu Ramadani; Ulfa Safitri; Azizah Salsabilah; Inayah Wulandari; Jovita Anggreni (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
The tofu processing industry generates liquid and solid waste that requires proper environmental cost management and recording. This community service program aimed to improve partners' understanding and skills in implementing environmental accounting at UD. Nur Jaya, Palopo City. The main problem identified was the use of a manual financial recording system that did not separate environmental costs from operational expenses. The program employed a Participatory Action Research (PAR) approach consisting of observation, development of training modules and recording instruments, training and mentoring, and evaluation. Program effectiveness was evaluated through pre-test, post-test, observation, and interviews. The results demonstrated improved partner understanding of environmental accounting, as reflected in the ability to identify five environmental cost components and independently prepare environmental cost records. The partner also consistently applied the recording format for three consecutive operational days, with net waste management costs ranging from IDR 3,330,000 to IDR 3,802,000 per day. The program produced a practical environmental accounting module and an environmental cost recording format to support more transparent and sustainable business management.